Dampak Peralihan Pengunaan Web 3.0 bagi Ilmu Pengetahuan dan Edukasi Bidang Peternakan - Agni Ayudha Mahanani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The world wide web has improved significantly since its inception in the 90's. Currently we are using web 3.0 or third generation web which is semantic and personal web. Previous studies have found that web 3.0 has been effectively used for various purposes such as business and education. Web 3.0 is considered capable of improving the user experience in meeting their information needs because it is more personal and real time and is able to meet user needs. Even though the benefits of using web 3.0 have been proven in previous studies, students and the public do not understand how web 3.0 can be used in the world of animal husbandry, therefore this journal will provide insight into how the web 3.0 platform can be used for study purposes and the livestock industry. . Through the use of a secondary data analysis approach, it was found that interesting and meaningful learning could potentially be delivered via the web 3.0 platform. There are several strategies to maximize the use of web 3.0 for learning. Among them are creating social media accounts, digitizing teaching materials and storing them in a cloud storage system, and personalizing teaching materials. In conclusion, web 3.0 can be used for learning purposes through the right strategy as found in this research. Students individually and in groups must improve their knowledge and skills in using web 3.0 for learning purposes. The limitation of this study is that the data were collected from secondary sources only. Future research will need to test through empirical environments to increase validity.